Conﬂictos discursivos: un estudio de Adiós, Ayacucho desde la perspectiva del análisis crítico del discurso - Mere Collazos, Milagros (2018)
Analyzes the novel Goodbye, Ayacucho of Julio Ortega from the critical analysis of the Discourse (ACD) that allows to observe the resources used by the narrator to demonstrate the social differences and demands of the disadvantaged represented in the novel, those who express a clearly distinguishable discourse. Part of the premise: in the literary works, the discourse used by the narrator, provides information on the story told and visualizes the relationship established between the different actors of a society at a given time. Indeed, the various modes of interaction between social groups over time have caused some to acquire more power than others, which is evident in and through the use of language.